Correction: Nishimura et al. Charge Exchange Spectroscopy of Multiply Charged Erbium Ions. Atoms 2023, 11, 40 - Yuki Nishimura; Saki Imaizumi; Hajime Tanuma; Nobuyuki Nakamura; Yuichiro Sekiguchi; Shinya Wanajo; Hiroyuki A. Sakaue; Daiji Kato; Izumi Murakami; Masaomi Tanaka; Gediminas Gaigalas (Atoms)
The journal’s Editorial Office and Editorial Board are jointly issuing a resolution and removal of the Journal Notice linked to this article [...]